Novel circular DNA virus identified in Opuntia discolor (Cactaceae) that codes for proteins with similarity to those of geminiviruses. (2nd November 2021) - Fontenele, Rafaela S.; Köhler, Matias; Majure, Lucas C.; Avalos-Calleros, Jesús A.; Argüello-Astorga, Gerardo R.; Font, Fabián; Vidal, Andreza H.; Roumagnac, Philippe; Kraberger, Simona; Martin, Darren P.; Lefeuvre, Pierre; Varsani, Arvind
Abstract : Viral metagenomic studies have enabled the discovery of many unknown viruses and revealed that viral communities are much more diverse and ubiquitous than previously thought. Some viruses have multiple genome components that are encapsidated either in separate virions (multipartite viruses) or in the same virion (segmented viruses). In this study, we identify what is possibly a novel bipartite plant-associated circular single-stranded DNA virus in a wild prickly pear cactus, Opuntia discolor, that is endemic to the Chaco ecoregion in South America. Two 1.8 kb virus-like circular DNA components were recovered, one encoding a replication-associated protein (Rep) and the other a capsid protein (CP). Both of the inferred protein sequences of the Rep and CP are homologous to those encoded by members of the family Geminiviridae . These two putatively cognate components each have a nonanucleotide sequence within a likely hairpin structure that is homologous to the origins of rolling-circle replication (RCR), found in diverse circular single-stranded DNA viruses. In addition, the two components share similar putative replication-associated iterative sequences (iterons), which in circular single-stranded DNA viruses are important for Rep binding during the initiation of RCR. Such molecular features provide support for the possible bipartite nature of this virus, which we named utkilio virus (common name of the Opuntia discolor in South America) components A and B. In the infectivity assays conducted in Nicotiana benthamiana plants, only the A component of utkilio virus, which encodes the Rep protein, was found to move and replicate systemically in N. benthamiana . This was not true for component B, for which we did not detect replication, which may have been due to this being a defective molecule or because of the model plants ( N. benthamiana ) used for the infection assays. Future experiments need to be conducted with other plants, including O. discolor, to understand more about the biology of these viral components.